Provenance evolution of the northern Weihe Basin as an indicator of environmental changes during the Quaternary. (17th April 2019) - Zhang, XY; He, MY; Wang, B; Clift, PD; Rits, DS; Zheng, Y; Zheng, HB
Abstract: The Weihe Basin is an intracontinental rift basin in central China that provides an ideal location for studying the interactions between regional tectonics and monsoonal climate change. In this paper, we present detrital zircon U–Pb ages from sediments from Core LYH drilled in the northern margin of the basin. We use these to illuminate changing sediment transport processes, provenance and palaeo-environments during the Quaternary. The sediments are dominated by zircon age groups of 100–400 Ma and 400–550 Ma, and three secondary age peaks at 700–1100 Ma, 1700–2100 Ma and 2400–2600 Ma. Multidimensional scaling plots support the conclusion that the Central Loess Plateau and the Luo River are the dominant sources of sediments to the core site. Before c . 1.06 Ma, the Qinling Mountains and the Wei River, as well as the Yellow River, had minor influence on the sedimentation at the core site. These results are consistent with the existence of a palaeolake prior to 1.06 Ma, which allowed sediments supplied to the south and east edge of the basin to be reworked to the northern side of the Weihe Basin. Subsequently, the Luo River has provided a steady source of sediments to the northern Weihe Basin.